Cortical activation changes in patients suffering from post-stroke arm spasticity and treated with botulinum toxin a - Tomášová, Zuzana; Hluštík, Petr; Král, Michal; Otruba, Pavel; Herzig, Roman; Krobot, Alois; Kaňovský, Petr (Journal of neuroimaging, 2013)
BACKGROUND AND PURPOSE: Botulinum toxin (BoNT) treatment relieves focal arm spasticity after stroke, likely acting at several hierarchical levels of the motor system. The central correlate of BoNT-induced spasticity relief may be detected using repeated functional MRI (fMRI) during motor task. METHODS: Five patients (4 males, 1 female, mean age 67 years) with hemiparesis and distal arm spasticity after chronic ischemic stroke were studied. FMRI was performed while moving the paretic hand in three sessions: before and 4 and 11 weeks after BoNT treatment. RESULTS: Arm spasticity significantly decreased following BoNT treatment across the group (mean modified Ashworth scale change .6). FMRI prior to BoNT treatment showed extensive bilateral active networks, whereas post-BoNT activation was limited to midline and contralateral sensorimotor cortices, and the third examination, when the toxin effect has worn off, again showed extensive activation similar to pre-BoNT examination. Post-BoNT session 2 compared to sessions 1 and 3 demonstrated a significantly less activation in contralateral frontoparietal areas including inferior frontal, postcentral, and middle frontal gyri as well as transient crossed cerebellar activation. CONCLUSION: Relief of post-stroke arm spasticity may be associated with changes at several hierarchical levels of the cortical sensorimotor system, including the prefrontal cortex.
Keywords: cévní mozková příhoda; botulinum toxin; senioři nad 80 let; Movement; Sensorimotor Cortex; Humans; pohyb; senzorimotorický kortex; lidé středního věku; Middle Aged; Aged, 80 and over; mužské pohlaví; Stroke; functional magnetic resonance imaging; paže; Evoked Potentials; evokované potenciály; nervosvalové látky; Botulinum Toxins, Type A; botulotoxiny typu A; arm spasticity; výsledek terapie; finger movement; Arm; Treatment Outcome; svalová spasticita; ženské pohlaví; lidé; Aged; Muscle Spasticity; Neuromuscular Agents; senioři; Male; Female